ANALYSIS OF TRUST IN THE FREE NUTRITIOUS MEAL PROGRAM AND PARENTING STRESS AMONG PARENTS OF SCHOOL-AGED CHILDREN - Firnanda Erindia; Akhmad Huda (Zaitun : Jurnal Ilmu Kesehatan, 2026)
Free Nutritious Meals Program (Program Makan Bergizi Gratis/MBG) is a government initiative aimed at improving the nutritional status of school-aged children. However, parents' trust in its implementation varies and may be associated with their psychological well-being in the context of parenting. This study aimed to examine the relationship between parents' trust in the Free Nutritious Meals Program and parenting stress among parents of school-aged children. A cross-sectional study design was employed involving a population of 122 parents of students enrolled in public elementary schools in Lamongan Regency. A total of 94 respondents were selected using a simple random sampling technique. Data were collected using a questionnaire measuring trust in the Free Nutritious Meals Program based on the trust model proposed by Mayer, Davis, and Schoorman, along with the Parenting Stress Index–Short Form (PSI-SF). Data were analyzed using Spearman's rank correlation test with a significance level of p < 0.05. The results showed that most respondents had a moderate level of trust in the Free Nutritious Meals Program (49 respondents; 52.1%) and experienced a moderate level of parenting stress (45 respondents; 47.9%). Spearman's rank correlation analysis revealed a significant negative correlation between parents' trust in the Free Nutritious Meals Program and parenting stress (p < 0.001; r = −0.512), indicating a moderate correlation. The findings suggest that higher levels of parental trust in the Free Nutritious Meals Program are associated with lower levels of parenting stress among parents of school-aged children.